Independent curriculum management in high schools implementing the force 2 driving school program in Indragiri Hilir district - Fitri Yanti; Heri Supriyana (Universitas Negeri Semarang, 2026)
This research aims to analyze the planning, organization, implementation and evaluation of the independent curriculum at the High School Implementing the Batch 2 Driving School Program in Indragiri Hilir Regency. This research uses a qualitative type with a case study approach. Data collection techniques were carried out using interviews, observation and document study. The data analysis was carried out in the stages of data collection, data reduction, data display, and drawing conclusions/data verification. The informants in this research were the principal, deputy principal for curriculum, representative for student affairs, learning committee, and subject teachers. The results of the research show that the management of the independent curriculum at the High School Implementing the Batch 2 Driving School Program in Indragiri Hilir Regency shows that: (1) in planning, receiving assistance in the form of learning committee training for school principals and teachers by the Ministry of Education, Culture, Research and Technology through school facilitators, holding In House Training (IHT) in schools for teachers, analyzing the characteristics of education units and preparing the school's vision and mission; (2) organization is carried out by developing a curriculum structure and intracurricular learning program, a project to strengthen the profile of Pancasila students, and extracurricular activities contained in the educational unit curriculum as well as dividing the roles and tasks of each field; (3) the implementation of the independent curriculum has been gradually carried out starting from differentiated learning, implementing projects to strengthen the Pancasila student profile, the use of technology in classroom learning, the existence of learning communities in schools, and the use of the independent teaching platform; and (4) evaluation and reflection are carried out at learning community meetings, performance observations, regular monthly meetings, end-of-semester meetings, end-of-year meetings as well as in the assistance of driving school facilitators.